Implantação e desenvolvimento de projetos no ciclo interdisciplinar da Prefeitura de São Paulo - Lacerda, Elaine Silva (2020)
This study focuses on municipal policy for the development and implementation of Projects with students from the public network of the Interdisciplinary Cycle of the Municipality of São Paulo, as a pedagogical proposal to mitigate the transition from the initial years to the final years of Elementary School, considering expectations present in this school reality. The hypothesis was stipulated that by centering teaching on the child and proposing that the project covers aspects of students' social and cultural reality, in addition to the dialogue between the areas of knowledge, as well as the relationship between practice and theoretical concepts, it is expected that the project method makes learning more meaningful and successful. Such policies were implemented based on the guidelines of Ordinance 5930/2013 (SÃO PAULO, 2013c) on the implementation and curricular reorganization of the Mais Educação São Paulo Program. It seeks to understand if and how the Project methodology can collaborate with the learning during the transition process, characterized by its ruptures and discontinuities in the pedagogical work. The research is based on the legal publications on the implementation policies of the Learning Cycles and the Project concepts proposed by William Heard Kilpatrick and John Dewey mainly. It was held in an elementary school, of the DRE Campo Limpo, of the City of São Paulo, through interviews with 5 teachers working in the Interdisciplinary Cycle, document analysis, as well as observation of the execution of the Project Times classes, in Shared Teaching in the 4th and 5th years, classes belonging to the Interdisciplinary Cycle and a questionnaire to the Pedagogical Coordinators of 43 elementary schools at DRE Campo Limpo. The results showed that methodological, formative and administrative deficiencies affected the positive results not to be presented in their entirety. And they indicated the need for improvements in the organization of time and space, democratization of work in shared teaching and the monitoring of actions